Implementasi Kebijakan Pengelolaan Dana Desa: Zaltman’s Metaphor Elicitation Technique - Saiful Anwar (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
The research objective is to investigate the suitability of village fund management policies with regulations in Indonesia. The study uses a qualitative approach with the Zaltman’s Metaphor Elicitation Technique (ZMAT) method. The data used are 2 fiscal years 2017-2018 in 5 villages in Semarang Regency. Village selection uses purposive sampling technique based on village economic growth. Based on the consensus map and the higher order construct the management of village funds sourced from the state budget is still inconsistent with regulations. RKPDes and APBDes planning are still far from the timeline provided by the regulation. The first stage disbursement process is not in accordance with regulations because of the existence of SiLPA. The financial statement information provided is not reliable because there is a difference between disbursement and realization. However, the village government continues to maintain accountability by disclosing village government financial reports. The ZMAT method which involved five villages with 25 informants and investigated the implementation of policies with regulations became the novelty of this study. This finding can be used as a regulatory evaluation tool by stakeholders in Indonesia. Keywords: Village Fund, APBN, ZMAT.